A stochastic evaluation for non-stationary random noise over a long time period based on local statinarity and its application to actual acoustics environment - Nashimura, K.; Ohta, M. (Archives of Acoustics, 2002)
A non-stationary environmental noise fluctuations can be treated as some composition of local state strips having arbitrary fluctuating pattern in a locally stationary time period. Its non-stationary characteristics can be seen in the form of its changing stage from a locally stationary state to another one by means of its temporal change of probability distribution. For a non-stationarity with continuously slow temporal change, the noise evaluation method is derived by considering the temporal change of moment statistics or distribution parameters. On the other hand, for a non-stationarity with stepwise rapid variation like an ON/OFF operation of machine, the noise evaluation method is derived by considering in principle the occurring probability of each of locally stationary state based on the mutually exclusive property. In the experimental consideration, the above contrastive two evaluation methods have been applied to actual cases with slowly changing environmental noise and rapidly changing machine noise.